Public engagement for public health: participatory budgeting, targeted social programmes, and infant mortality in Brazil. Issue 5 (3rd July 2020) - Touchton, Michael; Wampler, Brian
ABSTRACT: Brazil has made striking gains in public health since its democratisation in the mid-1980s. Previous research credits widespread economic growth and the creation of widespread social programmes for these improvements. We take a novel approach by also examining local participatory institutions. Participatory budgeting is a democratic innovation that allows residents to allocate a portion of the local budget directly to local needs, including healthcare. We evaluate whether participatory budgeting also influences infant mortality, a serious health problem facing Brazilian communities. We find that using participatory budgeting substantially reduces infant mortality, even more so when the programme is institutionalised.